A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Publisher: Springer Netherlands
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Ecological studies on Cryptopygus sverdrupi from Muhlig-Hofmannfjella, Antarctica - Sømme, Lauritz (Cryo-Letters, 1985)
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Studies of arthropod cold hardiness - Block, William; Sømme, Lauritz (British Antarctic Survey Bulletin, 1981)
Keywords: Antarktis; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cryptopygus sverdrupi n.sp. A new species of Collembola (Isotomidae) from Sverdrupfjella, Antarctica, with notes on related species in five genera - Lawrence, Peter N (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; leddyr

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

The entomology of Antarctica, with special reference to Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

On the soil fauna of the Antarctic and of the Sub-Antarctic Islands : the Oribatidae <Acari> - Dalenius, Per; Wilson, Ove (Arkiv för Zoologi: Serie 2, 1958)
Publisher: Almqvist & Wiksell Place: Stockholm
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; biologi; leddyr; zoologi